Tranformasi Digital Sebagai Epistemologis Model Pendidikan Calon Guru Agama Katolik di Era 4.0 - Suko suko; Suyitno Muslim (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2022)
Realizing the educational ideals of prospective Catholic religious teachers in Indonesia in the industrial era 4.0 leads to an epistemological model for implementing digitalization-based education. Digital transformation is a form of technological development that affects all aspects of human life and shapes the characteristics of today's generation. Changes in the world of technology have caused the educational world of prospective Catholic teachers to adapt in terms of models, strategies, methods, place and time in managing the educational process. Therefore, digital transformation literacy is the driving force that changes the face of the education model for Catholic teacher candidates in the 4.0 era. A systematic literature review is a way to examine the problems of Quo Vadis' education model for Catholic teacher candidates in the industrial era 4.0. De facto educational institutions for prospective Catholic teachers must be technology literate in educating generation 4.0 students. The education of this generation is inseparable from the influence of the development of the world of technology in educating prospective Catholic teachers to face educational challenges. Catholic religious education is challenged to change the way of teaching and learning in preparing prospective digital generations of Catholic teachers. Creative and innovative, the educational model for prospective Catholic teachers is directed at building an atmosphere of freedom of learning that utilizes digital media as an epistemological attitude of repentance and self-change to be able to carry out a learning process that cannot be separated from the digital world.